Hydrops fetalis caused by a blood group antibody usually undetected in routine screening. Issue 3 (November 1994) - Smoleniec, J; Anderson, N; Poole, G
Abstract : A case of isoimmunisation in pregnancy caused by antibodies to the Kpa red blood cell antigen is described. The preceding pregnancy had resulted in fetal hydrops for which no cause was found as the antibody screening cells used to investigate the fetal hydrops were Kpa negative. This case emphasises the importance of serological screening at a reference laboratory for low frequency red cell antigens before a diagnosis of non-immune hydrops is made.